Today, there are specific issues of the tax debt collection mechanism in our country - O‘taganov Anvar Nurxonovich (Genius Journals, 2024)
This article discusses the improvement of the tax collection mechanism, improvement of taxpayer service and training, simplification of the tax system and procedures, development of effective communication channels between taxpayers and tax authorities, improvement of tax collection mechanisms. In addition, theoretical and practical aspects of trends in the development of relations consisting in the formation of trust and perception of justice and the use of effective enforcement measures increase compliance.
Keywords: local tax; market value of property; cadastral value